2009
DOI: 10.7863/jum.2009.28.8.1043
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Power Doppler Angiography of Cyclic Ovarian Blood Flow

Abstract: The VI would suffice as the principal vascular parameter for 3D power Doppler analysis. Preovulatory scans may be more useful for distinguishing pathologic vascularization. Hormonally suppressed ovaries have significantly lower vascularity throughout the cycle. Normal-appearing ovaries with vascular indices above the normal ranges established by these data may warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In summary, these data demonstrate that DCE‐US provides a sensitive, minimally invasive method to detect changes to vascular flow and volume in the dominant structures of the primate ovary (peri‐ovulatory follicle and corpus luteum). This method appears to be superior to other methods to detect vascular flow in ovarian tissues, given the statistical significance demonstrated with a relatively small number of research subjects compared with other Doppler‐based methods . In addition, abnormalities are readily detected by DCE‐US that might be difficult to detect by conventional 3D Doppler ultrasound imaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, these data demonstrate that DCE‐US provides a sensitive, minimally invasive method to detect changes to vascular flow and volume in the dominant structures of the primate ovary (peri‐ovulatory follicle and corpus luteum). This method appears to be superior to other methods to detect vascular flow in ovarian tissues, given the statistical significance demonstrated with a relatively small number of research subjects compared with other Doppler‐based methods . In addition, abnormalities are readily detected by DCE‐US that might be difficult to detect by conventional 3D Doppler ultrasound imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the capillary bed of CL in macaques may not generate enough Doppler signal to accurately measure the resistance index, and lack of transvaginal probes for smaller macaque reproductive tracts further compounds this problem (as discussed by . But, a previous investigation on a large cohort of women with normal menstrual cycles (n = 18) using 3D power Doppler angiography also did not find any significant differences in vascularity index of the ovary between different phases of the menstrual cycle during serial scanning sessions . A larger (n = 90) study demonstrated changes in measurements of Doppler impedance (resistance index) to the CL and correlation between serum P and RI, but this study reported data from 61 normal menstrual cycles .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TV‐CDS is a non‐invasive ultrasound technique used clinically to evaluate pelvic organ perfusion. On color Doppler images, blood flow during periovulation in a normal ovarian interstitium (25) is indicated by a defined reticular shape. In our study, stripe‐shaped flow was observed around benign ovarian tumors, which is less adequate than the blood flow in normal ovarian interstitium.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently unknown if reduced ovarian blood flow is the cause or consequence of CIA and follicular apoptosis. Ovarian blood flow changes throughout the menstrual cycle [50]. Ovarian blood flow peaks during the preovulatory phase and plateaus during the luteal phase [48][49][50].…”
Section: Chemotherapy and Ovarian Blood Flowmentioning
confidence: 99%